2009
DOI: 10.1128/aem.01837-08
|View full text |Cite
|
Sign up to set email alerts
|

Pichia anomalaDBVPG 3003 Secretes a Ubiquitin-Like Protein That Has Antimicrobial Activity

Abstract: The yeast strain Pichia anomala DBVPG 3003 secretes a killer toxin (Pikt) that has antifungal activity against Brettanomyces/Dekkera sp. yeasts. Pikt interacts with ␤-1,6-glucan, consistent with binding to the cell wall of sensitive targets. In contrast to that of toxin K1, secreted by Saccharomyces cerevisiae, Pikt killer activity is not mediated by an increase in membrane permeability. Purification of the toxin yielded a homogeneous protein of about 8 kDa, which showed a marked similarity to ubiquitin in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 59 publications
1
26
0
1
Order By: Relevance
“…This preliminary characterisation showed that KwKt and Pikt are stable within a pH range from 3 to 5 and at temperatures below 35°C, and that they maintain their killer activities for at least 10 days in wine. Further characterisation of Pikt has indicated that this toxin is a ubiquitin-like protein with an apparent molecular mass of 8 kDa (De Ingeniis et al 2009). A more recent study (Comitini et al 2009a) carried out in grape must and wine showed that K. wickerhamii and P. anomala can indeed control Brettanomyces/Dekkera spoilage yeasts.…”
Section: Screeningmentioning
confidence: 98%
“…This preliminary characterisation showed that KwKt and Pikt are stable within a pH range from 3 to 5 and at temperatures below 35°C, and that they maintain their killer activities for at least 10 days in wine. Further characterisation of Pikt has indicated that this toxin is a ubiquitin-like protein with an apparent molecular mass of 8 kDa (De Ingeniis et al 2009). A more recent study (Comitini et al 2009a) carried out in grape must and wine showed that K. wickerhamii and P. anomala can indeed control Brettanomyces/Dekkera spoilage yeasts.…”
Section: Screeningmentioning
confidence: 98%
“…The killer toxin Pikt produced by the P. anomala DBVPG 3003 strain was active on 15 isolates belonging to the genus Dekkera/Brettanomyces, and its fungicidal effect in wine was maintained during at least 10 days [69]. Further research revealed that this toxin presented a ubiquitin-like peptide structure with a molecular mass of approximately 8 kDa, and that it selectively interacts with β-1,6 glucans, which are the putative binding sites for Pikt on the cell wall of the sensitive targets [70]. Recently, the killer toxin KTCf20 secreted by the strain W. anomalus Cf20 was also suggested to bind to β-1,3 and β-1,6 glucans of the cell wall of sensitive strains.…”
Section: W Anomalus Produces Killer Toxins Of Broad Spectrummentioning
confidence: 99%
“…There is an amazing diversity of characterised killer proteins, with molecular masses ranging from 8 kDa to more than 300 kDa (De Ingeniis et al 2009;Kagiyama et al 1988); however, this diversity in protein size may arise mainly from different levels of glycosylation. An extremely heat-stable killer protein has been observed in one strain (Vustin et al 1989).…”
Section: Antimicrobial Activitymentioning
confidence: 99%